The role of insecure and fearful attachment styles in sexual risk behaviors among HIV-positive women attending a support group in Ibadan, Nigeria (2010)
The present study investigated the relationship between adult attachment style and unprotected sex among women living with HIV-positive in Ibadan. HIV-positive participants (N = 60) completed questionnaires assessing consistent condom use three months preceding study, multiple sexual partners, adult attachment, self-esteem, and depressive symptoms. Results revealed that insecure attachment styles (particularly negative attachment representations of self) and fearful attachment were associated with both number of none condom use in the past three months and having multiple sexual partners in the same period. Similarly negative self esteem and depressive symptoms were related to these high risk sexual practices. These relationships remained significant after controlling for self-esteem, and depressive symptoms. These results suggest the inclusion of relational factors such as attachment in HIV prevention.